PERISTIWA ENTREPRENEURIAL: TINJAUAN DAN PENGEMBANGAN PEMIKIRAN SHAPERO DALAM CERITA TIGA WIRAUSAHA DI BALI - Roni Tua (Jurnal Administrasi Bisnis, 2022)
The corpus of academic literature on entrepreneurship is progressing rapidly, which could lead to negligence for classical ideas that may still be pertinent and contextually necessary to be developed. The unanswered topic of what attributes attach to an entrepreneur and give rise to the label "entrepreneur" may be advanced after scholars revisit earlier theories. This study is a re-examination of Albert Shapero's notion of the displaced entrepreneur and his classical theory of entrepreneurial event, both of which have been useful in understanding the transition and intention of individual entrepreneurship: an artshop owner, a maker and an exporter of creative products. This study uses a qualitative technique to compare the experiences of three Bali-based creative product entrepreneurs. This study produces findings, confirmation of the crucial importance of prior employment, the potential entrepreneur's place of employment, and a crucial step in partnership building. The conclusions have significance for both theoretical and practical formulations of relevant and contextualised entrepreneurship development strategies.